The Economic Value of Changing Mortality Probabilities: A Decision-Theoretic Approach - Weinstein, Milton C.; Shepard, Donald S.; Pliskin, Joseph S. (Quarterly Journal of Economics, 1980)
Properties of individual willingness to pay for changes in mortality probabilities are examined using a decision-theoretic model. There is no unique value per life saved. The willingness to pay for a mortality reduction depends not only on the amount of reduction but also on the initial probability level and on whether the valuation is ex ante (e.g., decisions regarding health insurance, preventive medicine, or environmental health) or ex post (e.g., acute medical care). Several inequalities relating the imputed willingness to pay in various paradigm decision contexts are derived from the model with the addition of few additional behavioral assumptions.